The Evolution of Culture and its Influence on Modern Society (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes the stages of the evolution of culture, the main factors and its impact on modern society. Culture, as a historical process, is constantly changing and developing in connection with technology and social connections. In today's globalization, culture is not only limited to national traditions, but also formed through new concepts, such as digital technologies, artificial intelligence. The main purpose of the article is to cover modern cultural development processes and identify future trends.